2023
DOI: 10.3389/fmed.2023.1289528
|View full text |Cite
|
Sign up to set email alerts
|

Incisional surface quality of electron-beam irradiated cornea-extracted lenticule for stromal keratophakia: high nJ-energy vs. low nJ-energy femtosecond laser

Jian S. Chan,
Evelina Han,
Chris H. L. Lim
et al.

Abstract: IntroductionCorneal lenticules can be utilized as an additive material for stromal keratophakia. However, following extraction, they must be reimplanted almost immediately or cryopreserved in lenticule banks. Electron-beam (E-beam) irradiated corneas permit room-temperature storage for up to 2 years, enabling keratophakia to be performed on demand. This study aims to compare the performance of high nano Joule (nJ)-energy (VisuMax) and low nJ-energy (FEMTO LDV) femtosecond laser systems on the thickness consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(50 reference statements)
1
0
0
Order By: Relevance
“…For excimer laser systems (ablative procedures), it has been shown that reducing pulse energy is a key driver in reducing roughness [16]. This has been also empirically demonstrated for femtosecond systems [17,18]. Both correspond to our simulation findings and also shared in laboratory experiences with excimer ablation procedures [19].…”
Section: Discussionsupporting
confidence: 85%
“…For excimer laser systems (ablative procedures), it has been shown that reducing pulse energy is a key driver in reducing roughness [16]. This has been also empirically demonstrated for femtosecond systems [17,18]. Both correspond to our simulation findings and also shared in laboratory experiences with excimer ablation procedures [19].…”
Section: Discussionsupporting
confidence: 85%